Pengukuran Tingkat Kepuasan Pelayanan Pusat Penelitian dan Pengabdian Kepada Masyarakat - Fitri Masito; Yeti Komalasari; Nining Idyaningsih; Syukri Hamzah; Hadi Winarto (Politeknik Penerbangan Makassar, 2022)
This research was conducted to determine the level of satisfaction of research center services and community service. In the current era of openness, the Community Satisfaction Survey helps with two-way communication between service users. Through SKM, service users can directly convey expectations and inputs aimed at improving the optimal quality of service. The type of research used in this study is a quantitative type using a likert scale. This study aims to measure the level of satisfaction of research center services and community service through research questions on google forms on lecturers and tested for validity and reliability in their research instruments. The implementation of lecturer services by the Palembang Aviation Polytechnic, especially PusPPM services in 2020 generally reflects a good level of quality, with an IKM value of 3.35 or after being converted to 83.75 for research and for PKM the IKM value is 3.17 or after being converted to 79.25. The IKM value for SKM research is at an interval of 81.26 – 100 so it can be concluded that the quality of service is Very Good (A). While the IKM value for SKM PKM is at an interval of 62.51 - 81.25 so that it can be concluded that the quality of service is Good (B).